Crop raiding around Lake Mburo National Park, Uganda - Rugunda, Grace Kagoro (African Journal of Ecology, 2004)
In areas around lake mburo national park, large wild animals wander in close proximity t human settlements. This poses serious conflicts in terms of crop damage. This integration of conservation with other land uses is difficult where densely settled agricultural land surrounds a protected area potentially containing problem animals, as it is the case for several parks in Africa and Asia. The intensity for crop raiding was quantified through the use of random crop quadrants/ plots and area estimated crop techniques in a portion of raided fields. The animal species concerned were documented from observations, footprint and any other marks left behind. Three variables were tested as predictors of damage, human population density, distance from the park boundary and session. In this study data is presented regarding crop loss in different seasons of the year analysis of the crop damage variation and animal species involved in crop loss. A diverse assemblage of animal foraged on substance crops and analysis of crop damage revealed significant crop depreciation by wild life
Keywords: Community; Conservation; Crop raiding; Wild life